Plasma and aqueous humor levels of Maresin-1 in patients with diabetic retinopathy - Gungor Kobat, Sabiha; Gul, Fatih Cem; Celik, Fatih; Liman Uzun, Seda; Savur, Fatma; Kasar, Kader; Aydin, Suleyman (Nature Portfolio, 2026)
The aim of this study was to evaluate plasma and aqueous Maresin-1 (MaR1) levels in patients with diabetic retinopathy (DR) and to examine the ability of these levels to distinguish proliferative diabetic retinopathy. The study included three age and gender-matched groups of 25 cataract patients with no diabetes mellitus (DM) or additional disease (C), 25 cataract patients with diabetes and no retinopathy (DM + C), and 25 cataract patients with diabetic proliferative retinopathy (DR + C). All the patients were examined with respect to age, gender, fasting plasma glucose and hemoglobin A1c (HbA1c). Phaco + IOL implantation was applied to all patients in all the groups, and aqueous samples were taken during the operation. The plasma and aqueous MaR1 levels were analyzed using enzyme-linked immunosorbent assays. The diagnostic performance of plasma and aqueous MaR1 levels in distinguishing the DR + C group from the C group was evaluated using receiver operating characteristic (ROC) curve analysis. A statistically significant difference was determined between the groups with respect to fasting plasma glucose, and HbA1c levels (p < 0.0167 for all parameters tested). The plasma MaR1 levels in group DR + C were determined to be statistically significantly lower compared to the C and DM + C groups (p < 0.001). The plasma MaR1 levels in group DM + C were determined to be statistically significantly lower compared to the C group (p < 0.001). The aqueous MaR1 levels in group DR + C were determined to be statistically significantly higher compared to the C and DM + C groups (p < 0.001, p < 0.001, respectively). No statistically significant difference was determined between the DM + C and C groups in respect of the aqueous MaR1 levels (p = 0.590). ROC analysis showed excellent discriminative performance of both plasma and aqueous MaR1 levels in distinguishing the DR + C group from the C group (AUC = 0.968 and 0.974, respectively; both p < 0.001). According to the results of the study, MaR1 levels were significantly lower in plasma and significantly higher in the aqueous humor in the DR + C group. ROC analysis indicated that both plasma and aqueous MaR1 levels showed good discriminative ability in distinguishing the DR + C group from the control group. These findings suggest that alterations in MaR1 levels may be associated with the inflammatory processes involved in diabetic retinopathy and may reflect disease-related biological changes in both systemic circulation and ocular tissues.
Keywords: Diabetic Retinopathy; Anti-Inflammatory Mediators; Plasma Mar1; Aqueous Mar1